A comparison of entrapped and covalently bonded laccase: Study of its leakage, reusability, and the catalytic efficiency in TEMPO-mediated glycerol oxidation. Issue 5 (3rd September 2018) - Hong, Chi Shein; Lau, Cindy Chin Yee; Leong, Chun Yi; Chua, Gek Kee; Chin, Sim Yee
Abstract: This article presents the comparison for reusability and leakage between entrapped and covalently bonded laccase and their performances towards the selective oxidation of glycerol. The reusability of immobilized laccase enzyme was studied by reacting a batch of immobilized laccase with ABTS for 15 cycles. The investigation of the leakage of immobilized laccase was carried out by storing the immobilized laccase in acetate buffer solution for 32 days. The data show that the retained enzyme activities of entrapped and covalently bonded enzyme after being reused for eight cycles were well above 60% and the leakages after storing for a month in the acetate buffer at 4 °C were well below 15%. The entrapped laccase coupled with TEMPO was found to perform better and gave a two-fold higher yield of glyceraldehyde and glyceric acid in the selective oxidation of glycerol compared to covalently bonded laccase. Hence, physical entrapment of laccase would be a suitable immobilization method in the laccase-mediated selective oxidation of glycerol.